Relationship between emotional labor, work stress, employee creativity, and turnover intention: study on Indonesian bank frontliners - Devi Intan Satyaningrum; Indi Djastuti (Diponegoro International Journal of Business, 2020)
This study examines the effects of emotional labor on work stress, employee creativity and turnover intention, and examines the role of work stress as a mediator. The study was conducted in a limited way to the 90 employees of the Semarang branch of the BTN bank frontliners. The analysis using SEM PLS suggested that emotional labor had a positive effect on work stress and turnover intention but was not significant on employee creativity. Furthermore, work stress has a negative effect on employee creativity and a positive effect on turnover intention, and in this study proves that work stress mediated the influence of emotional labor on employee creativity and on turnover intention.